Phylogeography of a Sahelian rodent species Mastomys huberti: a Plio-Pleistocene story of emergence andcolonization of humid habitats - (:unkn) unknown (My University, 2008)
The multimammate rat Mastomys huberti is a Sahelian species restricted to West Africa. Throughout its distribution area, the species is associated with humid habitats, flood plains and ponds, which make its current distribution highly fragmented. Knowing that humid and dry climatic phases regularly alternated along the Quaternary in West Africa, it can be postulated that the evolutionary history of the species and its genetic variation largely reflect these climatic oscillations. We used mitochondrial cytochrome b sequences to investigate the phylogenetic relationships of M. huberti populations across the totality of the species’ geographical range (Mali, Senegal, Guinea and Mauritania). We found that cytochrome b sequence variation is partitioned into four divergent clades (mean Kimura 2-parameter genetic distances varying from 0.57 to 3.08%) corresponding to distinct geographical regions. We dated the separation events of these clades between 0.93 and 0.17 million years ago, suggesting that M. huberti history was strongly influenced by the Quaternary climatic variations and related hydrographic network changes. Relationships between lineages and the partitioning of genetic diversity suggest the occurrence of two refuges along the Atlantic coast during arid periods. Moreover, the species’ current range results from a stepwise colonization from west to east. M. huberti colonized recently the Inner Delta of Niger River in Mali, probably during a humid episode some 0.6 million years ago. Demographically stable and highly diversified populations were found in South Senegal and Guinea while populations in North Senegal and in Mali experienced low numbers followed by a demographic expansion during the African Humid Period (c. 14 800–5500 BP). During the last arid period (c. 23 000–18 000 years ago), Malian populations found refuge in the northern parts of the Inner Delta of the Niger River, then expended to the southern parts of the delta and along
Keywords: African Research